Regulating Private For-Profit Higher Education - Tierney, William (International Higher Education, 2012)
As the for-profit higher education industry continues to grow, many observers have questioned their practices and policies. The author explains why the industry continues to grow and proposes who will have to oversee and regulate the industry in the future.